Hubungan Antara Screen Time dengan Kemampuan Pragmatik Anak Usia 4-6 Tahun di TK Sri Juwita Hanum Surakarta - Aulia Adistyo, Dhiyah; Gunawan, Gunawan (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: Screen time is time spent engaging in "screen-based" behavior, such as watching television and using a smartphone, tablet, or computer. The impact of screen time can affect children's language skills, one of which is pragmatics. Pragmatics is a branch of linguistics that deals with the use of language in a social context. Objectives: This study aims to analyze and provide an overview of the "Relationship of Screen Time to Pragmatic Ability of Children Aged 4-6 Years in Sri Juwita Hanum Surakarta Kindergarten". Methods: This research is a quantitative research using a cross-sectional. research design. The sampling technique in this study was purposive sampling and the number of samples used was 33 respondents. The data in this study were analyzed univariately and bivariately, the statistical test used in this study used the coefficient contingency test. Results: In the coefficient contingency test results, the result of ρ value of 0.000 or ρ value of < 0.05 was obtained, has a correlation coefficient value of 0.707 which is in the strong category, and has a unidirectional correlation direction. Conclusion: There is a positive and strong correlation or relationship between Screen Time with a ρ value of 0.000, and a correlation coefficient value of 0.707 in children aged 4-6 years in Sri Juwita Hanum Kindergarten. Keywords : Screen time, Pragmatics, Children aged 4-6 years